Head First: The Language of the Head Voice - Striny, Denes (Hamilton Books, 2007)
Denes Striny's international singing career brought him to the major opera houses of the world in leading roles. At the same time, he was evolving his vocal technique in a quest to find his full vocal potential. This book documents his struggles and successes with himself, teachers, coaches, and other singers. Striny, while maintaining his singing career, also had a full studio of singers studying with him in New York City. In this his first book, Striny confronts and explains the universal problem in singing today. This problem is at the center of an important dilemma in the world of opera today-namely, where have all the great operatic voices gone? Striny dissects the problem and offers the solution, which is a return to singing in the "Head Voice," the only true operatic sound. For the past sixty years, the knowledge that there are thirty-two muscles, bones, ligaments, and sinewy masses of tissue located around the larynx led teachers and students to chase this anatomical knowledge in search of answers to vocal theories. However, they have not learned the basic fundamental truth-those who sing in the head voice are the only true operatic voices. The late Birgit Nilsson, international opera legend and long-time friend, mentor, and teacher to Striny, shares her insights with Striny and the reader throughout the book. Head First is a must for teachers, students, professional singers, and opera lovers who will gain valuable insight into the "voice of opera."